Techno-resonance innovation capability for enhancing marketing performance: A perspective of RA-theory - Lauw Sun Hiong; Augusty Tae Ferdinand; Erna Listiana (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
The current study is conducted to fill up the research gap on the inconsistent findings of the ability of market orientation in enhancing marketing performance through inserting the techno-resonance innovation capability and product innovativeness as factors to leverage marketing performance. Five hypotheses were developed and tested in a sample frame of 121 SMEs in the region of West Borneo, Indonesia. The findings of this study demonstrate the pivotal role of techno-resonance innovation capability in two folds. Firstly, a techno-resonance innovation capability is proved as a mediator of marketing orientation in enhancing marketing performance. Secondly, the techno-resonance innovation capability, which holds the potential for enhancing the product innovativeness, is essential but not sufficient to enhance marketing performance; still, another extra effort is necessary, such as resonating the value of innovativeness to the target market.
Keywords: M13; M310; O32; 650; market orientation; techno-resonance innovation capability; product innovativeness; market performance; Indonesia